Peran Motivasi Orang Tua Dalam Meningkatkan Hasil Belajar Bahasa Indonesia Kelas V Pada Program Belajar dari Rumah pada Masa Pendemi - Hani Haniatus Zahro'; Elvina Sulistiyani; Achlis Rizkiya; Moh. Sifahrul Fahmi; Retno Susilowati (JEID: Journal of Educational Integration and Development, 2021)
This study aims to describe the role of parents motivation in learning outcomes in the home learning program in the midst of the Covid-19 pandemic, difficulties of parents in teaching the learning from home program during the pandemic, as well as how to overcome the difficulties of parents in teaching during the COVID-19 pandemic. The problems studied in this study are what are the roles of parents’ motivation in learning outcomes the Covid-19 pandemic, how the implementation of the learning from home program (BDR) during the Covid-19 pandemic, and how the results and effectiveness of the home learning program (BDR) during the Covid-19 pandemic. This study used a qualitative descriptive method with data analysis in the form of a survey of teachers and communities in the village of Gandri, Sedan district, Rembang District. This results of this determination show that the role f parents in a pandemic like this is very important and meaningful for children. Parents are required to be teachers as well as motivators for children during the home learning program (BDR). The role of parents is very important for the results and effectiveness of children’s education.